Postharvest quality and shelf-life assessment of sweet pepper (Capsicum annuum L.) Under ambient storage conditions: Postharvest Quality of Sweet Pepper Genotypes - Nag, Arpita; Ferdousi, Jannatul; Islam, Md Shahidul; Nath, Dwipok Deb; Islam, S M Rejbanul; Hossain, Md Iqbal (Journal of the Sylhet Agricultural University, 2026)
Sweet pepper (Capsicum annuum L.) is a highly perishable, nutrient-rich vegetable, and maintaining its postharvest quality at room temperature is a major challenge. This study evaluated the fruit quality and shelf life of 11 (G1,G2,G3,G4,G5,G6,G7,G8,G9,G10,G11) sweet pepper genotypes stored at ambient storage conditions (24.73±0.21°C, 69.26±0.04% RH) for a period of 27 days. The experiment arranged in a Completely Randomized Design (CRD) was carried out under laboratory conditions with three replications over period of September 2024 to March 2025. The maximum respiration rate (1723 μmol g-1 s-1), TPC (130.98 mg 100g⁻¹ DW), carotenoids (0.849mg 100g⁻¹DW), and anthocyanin (1.08 mg 100g⁻¹ FW) were recorded in G7, and G10 had the highest chlorophyll b (0.102 mg g-1). Maximum vitamin C (173.46 mg 100g⁻¹ FW), TFC exhibited by G11 higher than other varieties. Significant quality reductions was occurred by day 20. At this stage, G5 retained the highest vitamin C (146.38 mg 100g⁻¹ FW) and DPPH activity (56.74%). G7 had higher retention of TPC (80.97 mg 100g⁻¹ DW), carotenoids (0.627 mg g-1 FW) and anthocyanin (0.22 mg 100g⁻¹ FW); while G9 and G10 were better in retaining the chlorophyll a (0.051 mg g-1 FW) and TFC (93.68 mg 100g⁻¹ DW). G4, G9 and G10 genotypes had longer shelf life (24.67, 25.61 and 26.67 days respectively) retaining the higher overall quality. Conversely, G1 and G2 had a shorter shelf life and poorer nutrient retention, associated with higher respiration rates. Thus, the genotypes G4, G9 and G10 are recommended to store for longer duration( 24-27 days) at room temperature with minimum loss in quality. However, it needs to verify again before being conferring final recommendation. J. Sylhet Agril. Univ. 12(2): 01-16, 2025